Seismic vulnerability assessment and characterisation of the buildings on Faial Island, Azores - Neves, F.J. (2012)
The earthquake of the 9th of July 1998 that hit in the central group of the Azores archipelago greatly affected the islands of Faial, Pico and São Jorge, reaching a magnitude of Mw 6.2 with the epicentre located about 15km northeast of the Faial Island. This earthquake allowed the collection of an unprecedented quantity of data concerning the characterisation of the building stock and the damage suffered by construction. This is the main purpose of this research, consisting essentially of three main aspects: (i) A detailed characterisation of the building stock, assigning a five category classification, from old traditional rubble stone masonry to reinforced concrete moment framed buildings; (ii) A detailed damage grade classification based on the different damage mechanisms observed; and, (iii) A seismic vulnerability assessment of the building stock. The results of the vulnerability assessment together with the building stock database and damage classification were integrated into a GIS tool, allowing the spatial visualation of damage scenarios, which is potentially useful for the planning of emergency response strategies and retrofitting priorities to mitigate and manage seismic risk.